Physicochemical characteristics of stingless bee honey from tetrigona apicalis / Hendrie Johann Muhamad Ridzwan … [et al.] - Muhamad Ridzwan, Hendrie Johann; Rosli, Nur Liena; Yusop, Mohamad Amir Shah; Mohammed, Anisah; Wan Razali, Wan Aizuddin (Universiti Teknologi MARA Cawangan Pahang, 2020)
Each log of stingless bee honey may produce different characteristics of honey due to the different geographical and resources of nectar. The aim of this study is to determine the physicochemical characteristics of stingless bee honey from Tetrigona apicalis species (T. apicalis) at different production logs in UiTM Pahang. The samples of stingless bee honey were collected from UiTM Pahang, Jengka Campus. Five different logs of stingless bee from T. apicalis were selected. There are five different parameters analysed in this study namely pH, total acidity, ash content, colour intensity, and moisture content. The findings showed that the pH for T. apicalis honey was acidic in a range of 3.31±0.01 to 3.43±0.02 with a total acidity of 126.67±5.77 to 152.33±6.43 meq/kg. The value of ash content was 0.240±0.03 to 0.490±0.03 g/100g while the moisture content was between 27-34%. The colour intensity of the honey was 0.83033±0.01 to 1.30523±0.01Abs with light amber and extra light amber colour. These findings are important to determine the physicochemical characteristics of stingless bee honey in UiTM Pahang and to measure the quality of honey that was produced.